Analysis Of The Relationship Between The Use Of Personal Protective Equipment, Knowledge And Workplace Accidents In Employees ATPTPAJ In 2022 - Rusli, Kenvin; Hutabarat, Vitrilina; Ariani, Peny (BEST Journal (Biology Education, Sains and Technology), 2024)
A work accident is an accident that occurs that is related to an employment relationship. The employment relationship here can mean that the accident occurred due to work or while carrying out work. Work accidents in general can be caused by two main things, namely unsafe work behavior (Unsafe Act) and unsafe working conditions (Unsafe Condition). Personal Protective Equipment (PPE) is a tool that has the ability to protect a person in a job whose function isolates the worker's body from hazards in the workplace. This study analyzes the relationship between the use of PPE, knowledge and the incidence of work accidents in employees at PT. PAJ Banyuasin City, South Sumatra in 2022. This study uses an Observational Analytical research design with a Cross Sectional approach. An overview of the results of the research in general is the number of respondents as many as 68 respondents who work as employees at PT. PAJ. For the age of respondents who have a minimum age of 20 years, the maximum age is 55 years and the average age of respondents is 25 years. There is a relationship between knowledge and the incidence of work accidents in employees at PT. PAJ Banyuasin City, South Sumatra. It is hoped that all employees will always be committed to the correct implementation of SOPs at work, especially in the use of PPE so that work accidents do not occur